2016
DOI: 10.1364/oe.24.000262
|View full text |Cite
|
Sign up to set email alerts
|

M-line spectroscopy on mid-infrared Si photonic crystals for fluid sensing and chemical imaging

Abstract: The presented work demonstrates the design and characterization of Si-based photonic crystal waveguides operating as an evanescent wave absorption sensor in the mid-IR range λ = 5-6 µm. The photonic crystal structure is fabricated in a Si slab upon a thin Si(3)N(4)/TEOS/Si(3)N(4) membrane. M-line spectroscopy is used to verify the presence of guided waves. Different fillings of the photonic crystal holes have been realized to avoid sample residuals in the holes and, at the same time, to obtain spectral tuning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For example, a sensor structure consists of parallel PC waveguides has been designed for fluid sensing and chemical imaging in Ref. [41]. Moreover, a holey and a slotted PC waveguide structures that are based on Si are designed to detect Triethylphosphate at MIR wavelength [42].…”
Section: Potential Fabrication Platform For Proposed Pc Based Sensormentioning
confidence: 99%
“…For example, a sensor structure consists of parallel PC waveguides has been designed for fluid sensing and chemical imaging in Ref. [41]. Moreover, a holey and a slotted PC waveguide structures that are based on Si are designed to detect Triethylphosphate at MIR wavelength [42].…”
Section: Potential Fabrication Platform For Proposed Pc Based Sensormentioning
confidence: 99%
“…We recently have worked on silicon based waveguides which interact with fluid samples placed in their evanescent fields, see, e.g. [30,31]. We expect that there will be significant developments in this spectral range as integrated photonics technology thus far is concentrated on the near infrared but condition monitoring applications would require mid-IR absorption data.…”
Section: Review On Selected Physical Sensor Devices and Device Princi...mentioning
confidence: 99%
“…Among the sensing approaches, optical techniques in the infrared fingerprint region of the investigated substance are particularly promising because of their high selectivity. The possibility to use photonic structures like waveguides for evanescent-wave absorption sensing was recently discussed for liquids [1]. Recently we also demonstrated that silicon waveguides with sub-wavelength dimensions can be used as sensing units for carbon dioxide detection [2].…”
Section: Introductionmentioning
confidence: 99%